Putting cocaine use and cocaine-associated cardiac arrhythmias into epidemiological and clinical perspective - Wood, David M (Blackwell Science Inc, 2010)
This is the first article in a series of three articles on cocaine-related cardiac arrhythmias, following on from the 2008 British Pharmacological Society Winter Meeting Clinical Section Symposium entitled ‘Cocaine induced cardiac arrhythmias – from ion channel to clinical treatment’. We will summarize the epidemiology of cocaine use across the world and in particular will focus on UK, Europe and US use prevalence data. We will discuss the acute cardiac and non-cardiac toxicity associated with cocaine and highlight the lack of data on the true UK prevalence of acute cocaine toxicity and on the incidence of cocaine-related cardiac arrhythmias.